Non sorted polygons in Terra Nova Bay area (Victoria Land, Antarctica) - BONDESAN A.; MENEGHEL M.; STENNI B.; SALVATORE, Maria Cristina (Terra Antartica Pubblication, 1997)
In the Terra Nova Bay fields of periglacial polygon are common. The develop on flat or gently sloping surfaces covered by a mantle of loose etherometric material, mainly of glacvial origin. The polygons have been described by topography, morphology and grain size analysis. Field data and interpretation suggest that the analized polygon fields are still covering ice bodies which represent the vanishing stage of previous larger glaciers, probably of Wisconsinian age.